PENGARUH LOAN TO DEPOSIT RATIO (LDR), CAPITAL ADEQUACY RATIO (CAR), NET INTEREST MARGIN (NIM) dan BIAYA OPERASIONAL DIBANDING PENDAPATAN OPERASIONAL(BOPO) TERHADAP RETURN ON ASSET (ROA) (Studi Bank Umum Konvensional tahun 2013 - 2019) - Murdiyanto, Agus (Dinamika Akuntansi Keuangan dan Perbankan, 2020)
This study aims to analyze the effect of the Loan To Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Net Interest Margin (NIM) and Operational Costs compared to Operating Income (BOPO) to Return On Assets (ROA) (Conventional Commercial Bank Studies 2013 to 2019). This research uses several analytical methods, namely descriptive analysis, Classic Assumption Test, Multiple Linear Regression Test. The LDR independent variable test results have a positive and not significant effect on the dependent variable ROA. CAR, NIM, BOPO have a negative and significant effect on the dependent variable ROA. Simultaneously there is a significant influence between Loan To Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Net Interest Margin (NIM) and Operational Costs Compared to Operating Income (BOPO) to Return on Assets (ROA). Adjusted R2 Return on Assets (ROA) can be explained by variations of the four independent variables Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Net Interest Margin (NIM) Variables, Operational Cost Variables compared to Operating Income (BOPO) . Keywords: ROA, LDR, CAR, NIM and BOPO